Pumpkin Crunch Enterprise / Eldalena Samsudin... [et al.] - Samsudin, Eldalena; Emaran, Emelia; Ahmad Shuhairi, Nor Shaziera; Mohd Sabri, Norhajar Atikah; Rosli, Rusydi (Faculty of Business Management, 2010)
Pumpkin Crunch Enterprise is a company that focuses on business retailing of pumpkin bars that operating their business in Warisan Square, which is situated at the heart of Kota Kinabalu, Sabah. The pumpkin bars is festive enough for the holidays and delicious enough for any occasion. Our company sells pumpkin bars to all race and religion. Although our product is base on dessert, but we also care about our customer health such as we reduce the uses of sugar while we make this dessert. We also choose health and best ingredient to make this pumpkin bars. The business has identified its target market as the people around of the town who is shopping and has another business. These are 3 major market segment within the target area : teenagers, families, and ordering service. The first group consists of about 800 teenagers from primary school, college, and universities.